Prevalence pregnancy outcomes of gestational diabetes mellitus (GDM) in Homagama D.D.H.S. area and validation of selected screening methods to detect GDM. - Ginige, P.S (My University, 2004)
Based on the standard OGTT results, the crude prevalence of GDM at Homagama DDHS area was 8.4 that 86 of the women who were diagnosed as having GDM belonged to the asymptomatic impaired glucose tolerance category, results show that the presence of glycosuria detected by performing benedicts test was an extremely sub optinal test to be used as a screening test for GDM. Following variables reported significant association with GDM during the univarient analysis (PO.05), but not so after the multiple logistic regression analysis. Maternal age above 35 years